THE EFFECT OF WORK TRAINING AND WORK ETHIC ON TEACHER PERFORMANCE THROUGH WORK MOTIVATION AT STATE VOCATIONAL HIGH SCHOOL 1 STABAT - Murti Khairani Lubis; Kiki Farida Ferine; Yohny Anwar (RADJA PUBLIKA, 2026)
This study aims to analyze the effect of job training and work ethic on teacher performance with work motivation as a mediating variable at State Vocational High School (SMK) 1 Stabat. The background of the study departs from the importance of improving vocational teacher performance through strengthening training, work ethic, and work motivation. This study uses a quantitative approach with a population of all ASN at SMK Negeri 1 Stabat totaling 89 people (PNS and PPPK), all of whom are used as samples (population research). Data were collected through a Likert scale questionnaire and analyzed using Partial Least Squares (PLS) with SmartPLS. The results showed that job training had a positive but insignificant effect on teacher performance, but a positive and significant effect on work motivation. Work ethic had a positive and significant effect on teacher performance and work motivation. Work motivation also had a positive and significant effect on teacher performance. Indirectly, job training through work motivation did not have a significant effect on teacher performance, while work ethic through work motivation had a positive and significant effect on teacher performance. The R² values of 0.811 for work motivation and 0.862 for teacher performance indicate that the model is able to explain a high proportion of the variance in both dependent variables. This finding confirms that work ethic and work motivation are key factors in improving teacher performance, while on-the-job training plays a greater role in boosting work motivation than directly influencing performance.